Muslims of Tobolsk Province in Second Half of 19th Century: Marriage Dynamics - G. Ch. Faizullina; E. N. Ermakova; L. Kh. Faizova (Научный диалог)
This study presents an analysis of the content of handwritten records from Muslim metric books of the mid-19th century at the Komarovskaya Yurt Mosque in Tobolsk Province. The analysis focuses on the second part, which includes information on marriages and divorces. Building upon previous research analyzing birth data from the first part of mosque records, this work introduces, for the first time, data on marriages and divorces of residents of Western Siberia belonging to a single ethnic group: the mosque’s parishioners were Bukharans — migrants from Central Asia. A total of 116 marriage records and six divorce records were analyzed. The statistics suggest that the institution of marriage was stable. The study reveals the ages of those getting married, marriage conditions, dowry amounts paid, reasons for divorce, and polygamy practices. It is proven that despite the lack of surnames among the Tatar population in the 19th century, recording the names of marrying individuals, their fathers, witnesses, and social status in mosque records allows for the identification of each individual. Interfaith marriage contacts were not recorded during the analyzed period. The relevance of this research lies in providing new insights into Muslim marriage customs and social processes in a specific territory during the specified period.